Immunopharmacology of free radical species - Blake, David (David R.); Winyard, Paul G. (Handbook of immunopharmacology. Cells and mediators., 1995)
Free radicals have been implicated in a entire host of different human disease states, which suggests that although they may not have a pivotal causal role, they are involved in the perpetuation of disease. In recentyears, it has become evident that although free radicals most certainly do have this role in perpetuating inflammatory reactions, they have perhaps a far more important role in acting as second messenger systems to maintain normal cell function. It is theperturbations of these reactions which pose the most intriguing therapeutic challenges. This volume deals with various basic mechanisms of free radical processes and injury. The emphasis in each case is on potential therapeutic strategies developing fromthis new knowledge.